CONTINUING EDUCATION IN HEALTH, DISCOURSE, AND TRANSFORMATION OF WORK IN THE SUS - Gaist, Leonardo; de Souza, Antonio Escandiel; Freitag, Vera Lucia (Seven Editora, 2026)
This study analyzes Continuing Education in Health (CEH) within the context of Primary Health Care (PHC), articulating its conceptual, political, and pedagogical foundations with the contributions of Critical Discourse Analysis (CDA). It assumes that CEH is a fundamental strategy for improving work processes in the Brazilian Unified Health System (SUS), promoting meaningful learning from the daily routine of services and the problematization of professional practices. The work discusses CEH as a social and political practice traversed by disputes over meaning, highlighting tensions between emancipatory perspectives—centered on dialogue, collective reflection, and the transformation of care—and technical-instrumental approaches aligned with managerial rationalities. Within PHC, it is emphasized that the effectiveness of continuing education depends on institutional, organizational, and subjective conditions that favor spaces for critical analysis of work. The overload of care, the precariousness of employment relationships, and the centrality of goals emerge as challenges that can limit its transformative potential. In this scenario, Critical Discourse Analysis is presented as a theoretical-methodological framework capable of revealing how scientific, normative, and institutional discourses produce effects on management, power relations, and the organization of care. It is concluded that the articulation between continuing education in health and critical discourse analysis broadens the understanding of formative processes within the Brazilian Unified Health System (SUS), highlighting that the transformation of health practices involves not only technical changes but also the problematization of ways of thinking, speaking, and giving meaning to work. Thus, continuing education reaffirms itself as a structuring axis for strengthening more democratic, comprehensive practices committed to social justice.DOI: https://doi.org/10.56238/sevened2026.008-108